Burnout Syndrome in the nursing team: reflection of the COVID-19 pandemic (Research, Society and Development, 2022)
Objective: To identify in the literature evidence on the factors that triggered Burnout Syndrome in nursing professionals caused by the Covid-19 pandemic. Methodology: This is a systematic review carried out using the Science Direct databases and the VHL (Virtual Health Library) platform. The review included studies with a quantitative and qualitative design of literature review, systematic review, narrative synthesis, cross-sectional and longitudinal studies published in any year in English and Portuguese. Results and Discussion: The search identified a total of 227 publications, after applying the criteria 24 articles were selected for reading and analysis in full and of these 8 articles were selected at the end of the study. The analysis of publications identified a greater concentration of studies in the year 2020, published in Iran, China and the United States. After the selection process, the three articles were analyzed and, through them, thematic dimensions were identified in three categories: 1) Studies that focused on the Burnout Syndrome related to the pandemic; 2) Studies that identified nurses as the target audience; 3) Impacts on nursing professionals who are on the front line. Conclusion: The study made it possible to understand the triggering factors of Burnout Syndrome in nursing professionals.